EFFECT OF PEPTIDES AND CITICOLINE ON EYE HEMODYNAMICS AND ENDOTHELIN LEVEL IN RETINITIS PIGMENTOSA - Mammadzada, A.N.; Kasimov, E.M.; Majidova, S.R.; Aliyeva, N.I. (World of Medicine and Biology, 2023)
Retinitis pigmentosa is the most common form of hereditary retinal dystrophy. To date, no approved therapy can stop the development of this disease or restore vision. The purpose of the study was to study hemodynamic parameters in the eye vessels and the level of endothelin-1 in the blood serum and tear fluid in patients with retinitis pigmentosa before and after using peptides and citicoline. 55 patients (110 eyes) diagnosed with retinitis pigmentosa aged 15–24 were examined. Doppler color flow mapping of the ophthalmic, central retinal, and posterior short ciliary arteries was performed. The level of endothelin-1 in blood serum and tear fluid was determined. The patients were treated with endonasal electrophoresis with Retinalamin and Omk1 instillation. All patients showed a statistically significant decrease in hemodynamic parameters in the central retinal artery and posterior short ciliary arteries and an increase in the level of endothelin-1. After treatment, hemodynamic parameters increase, and endothelin-1 levels decrease.